The lower body muscle activation of intermediate to experienced kayakers when navigating white water. Issue 8 (16th November 2016) - Murtagh, Misha; Brooks, Darrell; Sinclair, Jonathan; Atkins, Stephen
Abstract: In white-water kayaking, the legs play a vital part in turning, stabilising and bracing actions. To date, there has been no reported information on neuromuscular activation of the legs in an authentic white-water environment. The aim of the current study was to identify lower body muscle activation, using 'in-boat' electromyography (EMG), whilst navigating a white-water run. Ten experienced male kayakers (age 31.5 ± 12.5 yr, intermediate to advanced experience) completed three successful runs of an international standard white-water course (grade 3 rapids), targeting right and left sides of the course, in a zigzag formation. Surface EMG (sEMG) outputs were generated, bilaterally, for the rectus femoris (RF), vastus lateralis, biceps femoris and gastrocnemius, expressed as a percentage of a dynamic maximal voluntary contraction (dMVC). Only RF showed significantly higher activation than any muscle on the left side of the body, and only on the left side of the course ( P = .004; ETA 2 = 0.56). Other results showed no significant difference between muscle activation in the right and left legs during each run, nor when assessed at either the right or left side of the course ( P > .05). These findings indicate that contralateral symmetry in lower limb muscle activation is evident during white-water kayaking. This symmetry may provide a stable base to allow more asymmetrical upper body and trunk movements to be fully optimised. Lower body symmetry development should be considered useful in targeted training programmes for white-water kayakers.